Optical component and method for manufacturing optical component

By employing YAG single crystals with {211} planes for bonding and diffusion bonding, the challenges of growing large, void-free, and optically homogeneous laser media are addressed, resulting in improved thermal and optical performance for high-power lasers.

JP2025001174AActive Publication Date: 2025-01-08SHINKOSHA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023100626
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-20
Publication Date
2025-01-08
Estimated Expiration
2043-06-20

AI Technical Summary

Technical Problem

YAG single crystals, despite being desirable for their thermal conductivity and optical properties, are difficult to grow in large sizes and are expensive, while YAG ceramics suffer from lower thermal conductivity and optical inhomogeneities due to grain boundaries, and bonded laser medium assemblies often have voids at the interface.

Method used

The use of YAG single crystals with {211} planes as bonding surfaces for doped and undoped YAG crystals, combined with diffusion bonding at 1200°C to 1600°C and low pressure, to create a void-free and optically homogeneous laser medium assembly.

Benefits of technology

This method produces high-quality, large-sized optical components with minimal voids and uniform refractive index, enhancing thermal conductivity and optical performance for high-power lasers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025001174000002
    Figure 2025001174000002
  • Figure 2025001174000003
    Figure 2025001174000003
  • Figure 2025001174000004
    Figure 2025001174000004
Patent Text Reader

Abstract

To provide an optical component that has a large size, does not include a portion with non-uniform refractive index and is constituted of a YAG single crystal that has less voids at a joint interface, and to provide a method for manufacturing an optical component.SOLUTION: In an optical component, at least a joint surface of an undoped YAG single crystal is a {211} surface, a joint surface of a doped YAG single crystal and the joint surface of an undoped YAG single crystal are mirror polished and joined together, and then joined by diffusion junction by being subjected to pressure of 0.1 kPa or more and 10 kPa or less in a direction perpendicular to the joint surface at a temperature of 1200°C or more and 1600°C or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to optical components, such as laser gain media and fluorescent light-emitting devices, made of yttrium aluminum garnet single crystal material, and methods for manufacturing the optical components. [Background technology]

[0002] In fields such as laser processing, there is a demand for small, high-power, high-beam quality lasers. Recently, solid-state lasers using laser diodes (LDs) as excitation light sources have become widespread. Among them, yttrium aluminum garnet (hereafter referred to as "YAG") crystals doped with neodymium (Nd) or ytterbium (Yb) are the most widely used solid-state laser materials.

[0003] In order to realize a high-power output laser beam from a solid-state laser, the dissipation of heat generated in the solid, which is the laser gain material, is a major problem. As a method for effectively dispersing localized heat generation, it has been proposed to join a laser crystal doped with an optically active substance to a crystal not doped with an optically active substance, and the diffusion bonding method and direct bonding method have been devised (Patent Document 1).

[0004] Research on the structure of the laser medium has also progressed, and a method using a disk-shaped laser gain material is known. By forming the laser gain material into a thin disk shape, the receiving surface of the excitation light from the outside can be made large, and uniform cooling can be achieved over the entire disk surface. Among them, the reflective type (active mirror type) structure has attracted attention because it is possible to cool it with a heat sink or fluid by applying a reflective film to one surface of the thin film disk. Normally, the active mirror type structure improves mechanical strength and heat dissipation by joining a thin film disk doped with an optically active substance to a material not doped with an optically active substance (hereinafter, the integrated structure is called a "laser medium joint"). These materials require a large laser medium to handle high-power lasers, so transparent ceramic materials are used (Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4374415 [Patent Document 2] Patent No. 5330801 Summary of the Invention [Problem to be solved by the invention]

[0006] As a medium for solid-state lasers, YAG single crystals and polycrystalline YAG ceramics are used. Although YAG ceramics have the advantage that they can be easily made large and relatively inexpensively manufactured, they have the problem that their thermal conductivity is lower than that of single crystals due to the presence of grain boundaries, and that their thermal conductivity is particularly lower at low temperatures than that of single crystals. For this reason, it is desirable to use YAG single crystals as a laser medium, but there are problems with growing large single crystals, such as the difficulty and high cost of crystal growth, and the tendency for optical inhomogeneities such as refractive index (which are usually likely to occur in the center of the crystal, hereafter referred to as the "core") to occur during crystal growth.

[0007] In addition, because the laser medium bonded bodies in which crystals are bonded are bonded by overlapping smooth polished surfaces, voids are likely to occur at the interface. Although voids are small in size and are thought to have almost no effect optically, it is preferable for high-power lasers to have no voids. In order to improve thermal diffusion even if only slightly, it is also desirable to have no voids at the bonded interface.

[0008] The present invention has been made in consideration of these problems, and aims to provide a large optical component made of a single crystal that does not contain any inhomogeneous refractive index parts and has few voids at the bonding interface, and a method for manufacturing the optical component. [Means for solving the problem]

[0009] In order to achieve the above object, the optical component according to the present invention is a joint between a doped YAG single crystal, which is an yttrium aluminum garnet single crystal doped with an optically active substance, and an undoped YAG single crystal, which is an yttrium aluminum garnet single crystal not doped with an optically active substance, and is characterized in that the joint surface of the undoped YAG single crystal is a {211} plane.

[0010] The optical component according to the present invention is characterized in that the bonding surface of the doped YAG single crystal is a {211} surface.

[0011] The method for manufacturing an optical component according to the present invention is characterized in that the bonding surfaces of the doped YAG single crystal and the undoped YAG single crystal are mirror-polished and bonded, and then diffusion bonding is performed by applying a pressure of 0.1 kPa to 10 kPa in a direction perpendicular to the bonding surfaces in the atmosphere at a temperature of 1200°C to 1600°C.

[0012] The optical component according to the present invention comprises the doped YAG single crystal and the undoped YAG single crystal, <211> It is characterized in that the crystal is grown in the axial direction and the transmission surface is obtained perpendicular to the crystal growth direction.

[0013] In the present invention, the problem is solved by using the {211} plane of a YAG single crystal that is not doped with an optically active substance (hereinafter referred to as "undoped YAG") as a bonding surface, and bonding it to a YAG single crystal doped with an optically active substance (hereinafter referred to as "doped YAG") to form an optical component such as a laser medium bonded body.

[0014] YAG single crystals are grown using the Czochralski method and are generally fast growing and easy to grow. <111> It is produced by pulling it up in the axial direction. During this process, the YAG single crystal grown is prone to having a non-uniform refractive index in the center, called the core. <111> The YAG single crystal ingot produced by pulling in the axial direction has {211} planes on its side, and it is possible to avoid the core by obtaining a disk material with the {211} plane on the side as its main surface.

[0015] The inventors also developed a technology for growing large YAG single crystals without using expensive iridium crucibles (JP Patent Publication Nos. 2023-056860 and 2023-056861). This made it possible to efficiently obtain large YAG crystals with {211} planes as bonding surfaces that do not contain inhomogeneous parts at a relatively low cost.

[0016] The present inventors discovered that by making the bonding surface of the YAG single crystal the {211} plane, it is possible to significantly reduce voids at the bonding interface. <111> Since crystals are grown in the axial direction and cut perpendicular to the crystal growth direction to obtain the crystals, the {111} plane is generally used as the bonding surface. However, when the {111} plane is used as the bonding surface, voids are likely to form at the interface. In contrast, it was found that the number of voids is drastically reduced by using the {211} plane as the bonding surface.

[0017] In the present invention, optical components such as a laser medium bonded assembly can be bonded by mirror-polishing the bonding surfaces of a YAG single crystal doped with an optically active substance and an undoped YAG single crystal, and then subjecting them to a heat treatment in air at a temperature of 1200°C to 1600°C and applying a low pressure of 0.1 kPa to 10 kPa perpendicular to the bonding surfaces.

[0018] In the present invention, doped YAG single crystals and undoped YAG single crystals are <211> After growing the crystal in the axial direction, the growth direction ( <211> It is effective to cut the crystal perpendicular to the growth direction (axial direction) and manufacture optical components such as disks. The method for growing large YAG single crystals developed by the inventors makes it possible to grow large crystals perpendicular to the growth direction while avoiding the core, and crystals can be obtained efficiently. Furthermore, it is possible to grow YAG single crystals doped with Nd or Yb. <211> By growing the crystal in the axial direction, it is possible to obtain a crystal with small concentration variation within the crystal and with the {211} plane as the bonding surface, avoiding the central core that occurs during growth. This makes it possible to efficiently manufacture optical components such as laser medium bonding bodies. Effect of the Invention

[0019] The present invention makes it possible to provide an optical component and a method for manufacturing an optical component that is made of a single crystal material that is free of pores or grain boundaries, has no core, and is a bonded body with extremely few voids at the bonding interface, and that has excellent optical properties and heat dissipation properties. [Brief description of the drawings]

[0020] [Figure 1] Czochralski method <111> Photograph of YAG single crystal grown in the axial direction [Diagram 2] Crossed Nicol photograph of a conventional crystal cut perpendicular to the crystal growth direction [Diagram 3] <111> Conceptual diagram of obtaining a disk-shaped crystal with {211} plane (a component constituting an optical component according to an embodiment of the present invention) from a YAG single crystal grown in the axial direction. [Figure 4] A photo of a conventional laser medium joint consisting of a {111} Nd-doped YAG single crystal and a {111} undoped YAG single crystal. [Diagram 5] Transmitted wavefront data of a conventional laser medium joint consisting of a {111} Nd-doped YAG single crystal and a {111} undoped YAG single crystal [Figure 6]A photo of a laser medium joint (optical component according to an embodiment of the present invention) in which a {111} Nd-doped YAG single crystal and a {211} undoped YAG single crystal are joined together. [Figure 7] Transmitted wavefront data of a laser medium joint (optical component according to an embodiment of the present invention) in which a {111} Nd-doped YAG single crystal and a {211} undoped YAG single crystal are joined [Figure 8] SEM image of the conventional bonding interface between {111} undoped YAG single crystal and {111} undoped YAG single crystal [Figure 9] SEM image of the interface between a {111} Nd-doped YAG single crystal and a {211} undoped YAG single crystal (optical component according to an embodiment of the present invention) [Figure 10] SEM image of the interface between a {211} Yb-doped YAG single crystal and a {211} undoped YAG single crystal (optical component according to an embodiment of the present invention) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, an embodiment of the present invention will be described in detail. Figure 1 (photo) shows a YAG single crystal grown by the Czochralski method. The crystal growth method is <111> When cut (sliced) in the axial direction perpendicular to the growth direction, an optically inhomogeneous area exists in the center of the crystal, as shown in Figure 2. For this reason, it is extremely difficult to obtain a large, high-quality crystal.

[0022] As shown in Figure 3, the core in the YAG single crystal is <110> Although they may extend in the axial direction, the {211} faces can be obtained parallel to the crystal growth direction and avoid the core. The inventors also developed a technique for growing large YAG single crystals without using expensive materials such as iridium, and by using this method it is possible to efficiently obtain disk-shaped crystals with {211} faces.

[0023] One method for fabricating a laser medium bonded body made of single crystal materials is to bond a crystal doped with an optically active substance to an undoped crystal by diffusion bonding or direct bonding. Diffusion bonding involves heat treatment at high temperatures, making it difficult to bond materials with different thermal expansion coefficients, but it has the advantage of being able to obtain a strong bond when the materials are the same, and not requiring expensive equipment. On the other hand, a method of directly bonding surfaces activated by an Ar beam or the like in a low-temperature high vacuum has also been put to practical use, but this requires expensive equipment. When joining crystals of the same type, such as doped YAG single crystals and undoped YAG single crystals, diffusion bonding is advantageous because it is relatively easy to achieve a strong bond. Diffusion bonding requires polishing the surface flat, but bonding is possible if the surface is a mirror-like surface with a surface roughness (Ra) of 0.5 nm or less, and the flatness is < λ / 2 (λ: 633 nm) over an area of ​​approximately φ50 mm, so no special polishing is required.

[0024] Heat treatment for diffusion bonding is performed in air at a temperature of 1200°C to 1600°C using an electric furnace or the like. During heat treatment, positioning is performed using a firing jig, and a load of 0.1 kPa to 10 kPa is applied in a direction perpendicular to the bonding surface of the doped YAG single crystal or (and) the bonding surface of the undoped YAG single crystal. This is sufficient, and bonding is possible without using a device such as a hot press. It is also possible to bond both crystals using a load due to their own weight. The load equivalent to their own weight is about 0.1 kPa. On the other hand, even if the load exceeds 10 kPa, the strength of the bond does not change. If the heat treatment temperature is less than 1200°C, the bonding strength may not be sufficient, and if it is 1600°C or higher, voids may grow at the interface.

[0025] Doped YAG single crystals and undoped YAG single crystals are usually <111> To grow the crystal in the axial direction, the disk is obtained by slicing it perpendicular to the axial direction. When a {111} doped YAG single crystal and a {111} undoped YAG single crystal are diffusion bonded, tiny voids may be generated at the bonded interface. Since the size of the voids is less than 1 μm, it is not considered to be a problem in normal use, but as a high-intensity laser medium, it is optically and thermally preferable for there to be few voids.

[0026] By using the {211} plane as the bonding surface of the YAG single crystal, it is possible to significantly reduce voids at the bonding interface. The {211} plane is a plane that is likely to appear as a facet during crystal growth and is considered to be a stable plane, so it is believed that using the {211} plane as the bonding surface reduces voids. When observing voids at the bonding interface between {111} planes, the {211} plane can sometimes appear in the void, so using the {211} plane as the bonding surface makes it difficult for voids to form. Note that as long as the bonding surface of at least the undoped YAG single crystal is the {211} plane, the bonding surface of the doped YAG single crystal may be the {211} plane or a plane other than the {211} plane.

[0027] YAG single crystals doped with Nd or Yb are used as laser media, and are generally grown from a melt using the Czochralski method, etc. When growing a crystal from a melt, the ratio of the doped element incorporated into the crystal varies depending on the element, and the segregation coefficient, which indicates the ratio, is approximately 0.2 for Nd and approximately 1.0 for Yb.

[0028] In the case of Nd-doped YAG single crystals, segregation is likely to occur, which makes it easy for a concentration gradient to form in the crystal growth direction. Therefore, if the crystal is grown parallel to the crystal growth direction, the concentration distribution within the surface will become large, which is not desirable. <111> When the crystal is grown in the axial direction, the {111} plane perpendicular to the crystal growth direction is used, but since the thickness is usually thin, it is hardly affected by optical inhomogeneity. Also, if the crystal is large, it is possible to obtain the crystal by avoiding the core. When a {111} Nd-doped YAG single crystal is joined to a {211} undoped YAG single crystal, the voids at the interface are significantly reduced compared to when a {111} Nd-doped YAG single crystal is joined to a {111} undoped YAG single crystal.

[0029] In contrast, in the case of Yb-doped YAG single crystals, the segregation coefficient is approximately 1.0, and there is almost no concentration gradient depending on the growth direction. <111> Even if the crystal is grown in the axial direction, it is possible to obtain the {211} plane in the vertical direction. By joining a Yb-doped YAG single crystal with a {211} plane and an undoped YAG single crystal with a {211} plane, a laser medium joint with fewer voids can be produced. Of course, as in the case of Nd-doped YAG single crystals, even if the {111} plane is joined to an undoped YAG single crystal with a {211} plane, a good joint with fewer voids at the joint interface can be obtained.

[0030] By using the technology to grow large YAG single crystals, <211> By growing the crystal in the axial direction, it is possible to obtain the crystal more efficiently. <211> It is possible to obtain a crystal by cutting it perpendicular to the growth direction from a crystal grown in the axial direction, avoiding the core. Not only for crystals that are not doped with optically active substances, but also for crystals that are doped with optically active substances, the crystals are cut perpendicular to the growth direction, so there is no concentration unevenness, and it is possible to obtain a crystal that avoids the core.

[0031] The technology related to optical components made of YAG single crystals as a laser medium described above can also be used for lighting that uses fluorescent materials doped with cerium (Ce).

[0032] <Example> Comparative examples and examples will be described below (see Table 1 below). First, a method for producing a crystal bonded body of the comparative example will be described. <111> The undoped YAG single crystal grown in the axial direction was cut perpendicular to the growth axis, ground, and the bonded surface was mirror-polished to produce a disk of φ54 mm × 6 mmt. <111> The crystals were grown in the axial direction, cut perpendicular to the growth direction, ground, and the bonded surfaces were mirror-polished to produce a disk with a diameter of 54 mm and a thickness of 1.6 mm. These two disks were then stacked, a weight of 1.3 kPa was applied, and the disks were bonded by heat treatment at 1500°C for 10 hours in air. The bonded crystals were then ground on the periphery and polished on both sides to obtain a bonded body with a diameter of 50 mm and a thickness of 5.2 mm (the thickness of the Nd:YAG single crystal was 0.2 mm). The appearance of the bonded body is shown in Figure 4. The measurement results of the transmitted wavefront accuracy using a laser interferometer (Verifire, manufactured by ZYGO) are shown in Figure 5. The transmitted wavefront accuracy was 0.89λ (λ=633 nm) in a diameter of 42.5 mm due to the influence of the core in the crystal.

[0033] The crystal joint of the embodiment will be described. <111> From the undoped YAG single crystal grown in the axial direction, a crystal was cut out parallel to the growth direction so that the {211} plane was the bonding surface, and the crystal was ground and the bonding surface was mirror-polished to produce a disk with a diameter of 54 mm and a thickness of 6 mm. For the Nd-doped YAG single crystal, a sample prepared in the same manner as in the comparative example was used. The appearance of the φ50 mm × 5.2 mm (thickness of the Nd:YAG single crystal was 0.2 mm) crystal bonded body prepared in the same manner as in the comparative example is shown in Figure 6, and the transmitted wavefront accuracy is shown in Figure 7. The transmitted wavefront accuracy was small, 0.12 λ, and good results were obtained because the core in the crystal was avoided (Example 1).

[0034] The crystal joint of Example 2 was the same as that of Example 1. <111> A disk with a diameter of 30 mm and thickness of 3 mm was prepared from an undoped YAG crystal grown in the axial direction so that the {211} plane was the bonding surface. A YAG single crystal doped with 5 at% Yb was also prepared. <111> The crystal was grown in the axial direction, and then cut out and processed parallel to the growth direction so that the {211} plane was the bonding surface, to produce a disk with a diameter of 30 mm and thickness of 1 mm. These two disks were then stacked on top of each other, and bonded by applying a load of 4.3 kPa to them and heat-treating them in air at 1500°C for 10 hours.

[0035] [Table 1]

[0036] Now, let us explain the observation of the bonded interface. Figure 8 shows a scanning electron microscope (SEM) image of the interface where the {111} plane of a doped YAG single crystal and the {111} plane of an undoped YAG single crystal were bonded by heat treatment at 1500℃ for 10 hours. Small voids of about 0.1μm can be seen here and there.

[0037] In contrast, Fig. 9 is an SEM photograph of the interface between the {111} plane of a Nd-doped YAG single crystal and the {211} plane of an undoped YAG single crystal, which were bonded by heat treatment at 1500°C for 10 hours (Example 1). Also, Fig. 10 is an SEM photograph of the interface between the {211} plane of a Yb-doped YAG single crystal and the {211} plane of an undoped YAG single crystal, which were bonded by heat treatment at 1500°C for 10 hours (Example 2). In both Examples 1 and 2, almost no voids were observed at the bonded interface, and it can be seen that the bond was good.

[0038] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various design modifications can be made to the present invention without departing from the scope of the claims.

Claims

1. An optical component which is a joint between a doped YAG single crystal, which is an yttrium aluminum garnet single crystal doped with an optically active substance, and an undoped YAG single crystal, which is an yttrium aluminum garnet single crystal not doped with an optically active substance, The bonding surface of the undoped YAG single crystal is a {211} surface. An optical component characterized by:

2. The bonding surface of the doped YAG single crystal is a {211} surface; 2. The optical component according to claim 1 .

3. A method for producing an optical component according to claim 1 or 2, comprising the steps of: the bonding surfaces of the doped YAG single crystal and the undoped YAG single crystal are mirror-polished and bonded together, and then the bonding surfaces are diffusion-bonded by applying a pressure of 0.1 kPa to 10 kPa in a direction perpendicular to the bonding surfaces in air at a temperature of 1200° C. to 1600° C.; A method for manufacturing an optical component comprising the steps of:

4. A method for producing an optical component according to claim 2, comprising the steps of: The doped YAG single crystal and the undoped YAG single crystal are grown in a <211> axis direction, and a transmission surface is obtained perpendicular to the crystal growth direction. A method for manufacturing an optical component comprising the steps of:

Citation Information

Patent Citations

  • Production of single crystal of garnet type structure

    JP1997202699A

  • Laser

    JP1999261137A

  • Manufacturing apparatus and manufacturing method of yttrium aluminum garnet single crystal

    JP2023056860A

  • Manufacturing apparatus and manufacturing method of yttrium aluminum garnet single crystal

    JP2023056861A

  • Optical composites between similar and between dissimilar materials

    US20100215890A1